THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON SALESPERSON PERFORMANCE - Wulandari, Wulandari; Darmawan, Didit (Jurnal Manajemen Bisnis dan Terapan, 2024)
Salesperson are the frontline connector between organizations and consumers. The attitude aimed at salespeople affects consumer perceptions and purchasing decisions that will be made. The emotions that salespeople experience have a big impact on their attitude. Businesses must be aware of how their salespeople interact with customers in order to build long-lasting partnerships and boost productivity. The purpose of the study is to ascertain how emotional intelligence affects salesperson performance in the Surabaya region. The research sample used 100 smartphone salesperson respondents who were still active in the Surabaya area and analyzed using multiple linear regression techniques which were previously tested for quality using validity, reliability, and classical assumption tests. The findings clarified that salesperson performance is positively and significantly impacted by emotional intelligence. The Adjusted R Square of 52.5% indicates the emotional intelligence variable's impact on salesperson performance.